Keunggulan Sekolah Dasar Islam: Perspektif Mutu Terpadu Pendidikan - Rizqiyana, Rizqiyana (IEMJ: Islamic Education and Management Journal, 2024)
This study aims to describe the excellence of SD Islam 01 YMI Wonopringgo in integrated quality management of customer-focused education, total involvement, measurement, commitment, and continuous improvement. This research uses the theory of Jerome S. Arcaro. This research used a descriptive qualitative approach. Data collection was done by conducting interviews, observation and documentation. Data analysis used in this research is done by reducing data, after which it is presented in the form of descriptions, and verified by drawing conclusions. The results showed that the advantages of education quality management at SD Islam 01 YMI Wonopringgo are contained in the 5 pillars of quality, including customers, total involvement, measurement, commitment, and continuous improvement.